Azure deploying websites. - Kennedy, Norm; Safari eBooks ([Place of publication not identified] : Intellezy, 2016)
"This course is designed to instruct students on Azure as it pertains to Virtual Networks, Virtual Machines, and Storage capabilities. Students will learn about PaaS Cloud Services, Understand the deployment environment, and create and configure PaaS Cloud Service. Students will work with upgrading Applications, understand communication between roles, understand PaaS to IaaS communication, scaling roles, and work with monitoring and alerts."--Resource description page.
Title from resource description page (Safari, viewed January 5, 2017).
Presenter, Norm Kennedy.
Keywords: Microsoft Azure (Computing platform); Cloud computing; Application software -- Development; Electronic books